Diretrizes para a construção de um mapa conceitual : uma abordagem através da geometria plana - Vieira, Osvaldo de Oliveira (2019)
This paper aims to present the guidelines for a conceptual map’s construction, which can be used as a pefagogical resource, with a approach through the teaching of a flat Euclidean Geometry, using LATEX as a programming tool, bringing a complete language of commands and clarifications of the pachages and libraries used, based on the methodology described by Marriott e Torres (2003) e Moreira (2012).The chosen content was the one of flat geometry. In the beginning of the work we briefly describe the emergence and development of geometry throughout history. Later, we describe the use of LATEX as a platform and and the packages that were essential in the construction of a programming language for the construction of the conceptual map. For the construction of the map he used the contents of flat geometry, focusing on his axioms, definitions and postulates of the book Dolce e Pompeo (2005). Therefore, it is expected that this material will foster the creation of new ideas for other products based on the use of this programming language to help obtain a more constructive teaching-learning, dynamic and meaningful teaching-learning for both teachers and students.